Comparison of ambulatory blood pressure monitoring and office blood pressure in primary health care of populations at a high risk of hypertension - Wei Gao; Yanwen Jin; Ting Bao; Yan Huang (Frontiers in Public Health, 2023)
IntroductionCurrent studies have found that the incidence of masked hypertension is high in Asian countries, but the use of ambulatory blood pressure monitoring (ABPM) in Asian countries is very limited, especially in primary health care. We compared the ABPM and office blood pressure (OBP) in primary health care of a high-risk population of hypertension.MethodsThe study included participants with at least one risk factor for hypertension who received primary health care. Demographic data, present medical history, personal history, and family history were collected by questionnaire.ResultsA total of 823 subjects were included in the study. There were 531 (64.5%) subjects with hypertension by ABPM and 316 patients (38.4%) by OBP. A paired chi-square test showed that the positive rate of ABPM in the diagnosis of hypertension was significantly higher than that of OBP (chi-square value 174.129, P < 0.0001). There were 24 (2.9%) patients with white coat hypertension, 239 (29.0%) with masked hypertension, 504 (52.9%) with a non-dipping pattern, 135 (16.9%) with nocturnal hypertension and 18 (2.2%) with high ambulatory BP variability. Concordance correlation coefficient showed there was a poor correlation between OBP and awake average BP. Scatter plot displayed there was a positive correlation between OBP and awake average BP, but the degree of fitting was not high. The Bland Altman plot showed that OBP and awake average BP were consistent.ConclusionsAlthough OBP and ABPM have some consistency, ABPM can screen for masked hypertension and nocturnal hypertension in primary care of populations at high risk of hypertension. Therefore, ABPM is necessary in the primary health care of populations at high risk of hypertension and can be used as a routine screening.